2015
DOI: 10.1111/tpj.12854
|View full text |Cite
|
Sign up to set email alerts
|

TRANSPARENT TESTA 13 is a tonoplast P3AATPase required for vacuolar deposition of proanthocyanidins in Arabidopsis thaliana seeds

Abstract: SUMMARYIntracellular pH homeostasis is essential for all living cells. In plants, pH is usually maintained by three structurally distinct and differentially localized types of proton pump: P-type H + -ATPases in the plasma membrane, and multimeric vacuolar-type H + -ATPases (V-ATPases) and vacuolar H + -pyrophosphatases (H + -PPases) in endomembranes. Here, we show that reduced accumulation of proanthocyanidins (PAs) and hence the diminished brown seed coloration found in the Arabidopsis thaliana mutant transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
82
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(86 citation statements)
references
References 46 publications
(104 reference statements)
2
82
1
1
Order By: Relevance
“…In Arabidopsis, AHA10 is required for the vacuolar accumulation of proanthocyanidins (Baxter et al, 2005) and has recently been shown to be localized at the tonoplast of seed coat endothelial cells (Appelhagen et al, 2015). In agreement with its preferential expression in the integument layers of developing seeds, no other phenotypes than the altered seed color have been reported for aha10 mutants.…”
Section: How Can Vacuoles Be Acidic Without V-atpase and V-ppase?mentioning
confidence: 86%
See 2 more Smart Citations
“…In Arabidopsis, AHA10 is required for the vacuolar accumulation of proanthocyanidins (Baxter et al, 2005) and has recently been shown to be localized at the tonoplast of seed coat endothelial cells (Appelhagen et al, 2015). In agreement with its preferential expression in the integument layers of developing seeds, no other phenotypes than the altered seed color have been reported for aha10 mutants.…”
Section: How Can Vacuoles Be Acidic Without V-atpase and V-ppase?mentioning
confidence: 86%
“…Although a slight increase of vacuolar pH was detected in the roots of wild-type, vha-a2 vha-a3, and fugu5-1 plants, vacuolar pH in the triple mutant fugu5-1 vha-a2 vha-a3 was not affected by ortho-vanadate ( Figure 7A). Moreover, although transcripts of AHA10, the only tonoplast-localized P-type H + -ATPase of Arabidopsis identified to date (Appelhagen et al, 2015), are detectable in roots, transcript levels are not increased in any of the V-ATPase and/or V-PPase mutants (Supplemental Figure 5B). In contrast, the V-ATPase inhibitor concanamycin A (ConcA) abolished vacuolar acidification in all genotypes tested, including vha-a2 vha-a3 and fugu5-1 vha-a2 vha-a3 ( Figure 7B), leading to the accumulation of autophagic bodies without affecting BCECF accumulation or vacuolar morphology ( Figure 7C).…”
Section: Vacuolar Acidification Is Abolished By the V-atpase Inhibitomentioning
confidence: 99%
See 1 more Smart Citation
“…The finding that blue flowering soybean (Glycine max) mutants have lesions in the apparent PH4 homolog (Takahashi et al, 2013) and that AHA10 is homologous and functionally interchangeable with PH5 (Appelhagen et al, 2015) suggests that the role of MBW complexes in vacuolar acidification is also widespread. The role of the MBW complex in specification of trichome or atrichoblast fate, by contrast, was established later in evolution as it is seen in some Rosid species only (Arabidopsis) and not in dicot species belonging to the Asterids or in monocots (Serna and Martin, 2006).…”
Section: Functional Divergence Of Mbw Complexesmentioning
confidence: 99%
“…PH3 promotes vacuolar acidification via activation of PH5, which encodes a tonoplast H + pump that is also required for tannin accumulation in the seed (Verweij et al, 2008). Because a mutation in the Arabidopsis PH5 homolog AHA10 also abolishes tannin accumulation in the seed (Baxter et al, 2005;Appelhagen et al, 2015), just like ttg2, it is likely that TTG2 enables tannin accumulation, at least in part, by activating AHA10.…”
Section: Functional Divergence Of Mbw Complexesmentioning
confidence: 99%